Are pine plantations valid tools for restoring Mediterranean forests? An assessment along abiotic and biotic gradients - Gómez-Aparicio, LORENA; Zavala, Miguel A.; Bonet, Francisco J.; Zamora, Regino (ECOLOGICAL APPLICATIONS, 2009)
The ecological impacts of forest plantations are a focus of intense debate, from studies that consider plantations as ``biological deserts{''} to studies showing positive effects on plant diversity and dynamics. This lack of consensus might be influenced by the scarcity of studies that examine how the ecological characteristics of plantations vary along abiotic and biotic gradients. Here we conducted a large-scale assessment of plant regeneration and diversity in plantations of southern Spain. Tree seedling and sapling density, plant species richness, and Shannon's (H') diversity index were analyzed in 442 pine plantation plots covering a wide gradient of climatic conditions, stand density, and distance to natural forests that act as seed sources. Pronounced variation in regeneration and diversity was found in plantation understories along the gradients explored. Low-to mid-altitude plantations showed a diverse and abundant seedling bank dominated by Quercus ilex, whereas high-altitude plantations showed a virtually monospecific seeding bank of Pinus sylvestris. Regeneration was null in plantations with stand densities exceeding 1500 pines/ha. Moderate plantation densities (500-1000 pines/ha) promoted recruitment in comparison to low or null canopy cover, suggesting the existence of facilitative interactions. Quercus ilex recruitment diminished exponentially with distance to the nearest Q. ilex forest. Richness and H' index values showed a hump-shaped distribution along the altitudinal and radiation gradients and decreased monotonically along the stand density gradient. From a management perspective, different strategies will be necessary depending on where a plantation lies along the gradients explored. Active management will be required in high-density plantations with arrested succession and low diversity. Thinning could redirect plantations toward more natural densities where facilitation predominates. Passive management might be recommended for low-to moderate-density plantations with active successional dynamics (e. g., toward oak or pine-oak forests at low to mid altitudes). Enrichment planting will be required to overcome seed limitation, especially in plantations far from natural forests. We conclude that plantations should be perceived as dynamic systems where successional trajectories and diversity levels are determined by abiotic constraints, complex balances of competitive and facilitative interactions, the spatial configuration of native seed sources, and species life-history traits.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: competition; environmental gradients; Facilitation; management strategy; Mediterranean forests; pine plantations; Regeneration; seed dispersal; species diversity; stand density

Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E. Torres; González, G. Montero; Suárez, M. A.; Cámara, D. E. L. A.; TORRES ÁLVAREZ, E.; Montero González, G.; Suárez de la Cámara, M. A. (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: cork-oak; Quercus suber; silviculture; stand density